Sequential BCMA CAR T-cell therapy in refractory multiple myeloma - Richardson, Tim; Holtick, Udo; Frenking, Jan; Tharmaseelan, Hishan; Balke-Want, Hyatt; Flümann, Ruth; Mai, Elias K.; Sauer, Sandra; Teipel, Raphael; von Bonin, Malte; Hallek, Michael; Scheid, Christof; et al. (Blood advances, 2025)
Multiple myeloma (MM) relapsing after B-cell maturation antigen (BCMA)-directed chimeric antigen receptor (CAR) T-cell treatment remains a therapeutic challenge. Data on re-exposure to CAR T-cell therapy targeting the same antigen are scarce. We analyzed 10 heavily pretreated patients with RRMM at 3 medical centers treated with the commercially approved CAR T-cell therapy product idecabtagene vicleucel in a real-world setting. Upon relapse, all patients received ciltacabtagene autoleucel as a second CAR T-cell therapy infusion, with bridging treatments permitted between both therapies. Sequential therapy with BCMA-directed CAR T-cell therapy was safe, with no higher-grade immune-cell-associated side effects or new safety signals. We found robust CAR T-cell therapy expansion and high response rates (100% with at least very good partial response, with 60% achieving minimal residual disease negativity), with an estimated progression-free survival of 64.8% (95% confidence interval, 39%-100%) at 6 months after the second CAR T-cell treatment. Duration of response to first CAR T-cell therapy was predictive for durable responses to the second CAR T-cell therapy product. Loss of BCMA antigen occurred in only 1 of 3 patients relapsing after ciltacabtagene autoleucel. Two of three relapsing patients died within a year, and showed no further response to bispecific antibody treatment. To our knowledge, this study provides the first real-world evidence that sequential treatment with 2 different commercially approved BCMA CAR T-cell therapy products is both feasible and effective, particularly in patients with prolonged responses to initial BCMA CAR T-cell therapy.
Online verfügbar 15 July 2025, Version des Artikels 13 September 2025
Gesehen am 20.01.2026